2016
DOI: 10.1002/adhm.201600026
|View full text |Cite
|
Sign up to set email alerts
|

Organ‐to‐Cell‐Scale Health Assessment Using Geographical Information System Approaches with Multibeam Scanning Electron Microscopy

Abstract: This study combines novel multibeam electron microscopy with a geographical information system approach to create a first, seamless, navigable anatomic map of the human hip and its cellular inhabitants. Using spatial information acquired by localizing relevant map landmarks (e.g. cells, blood vessels), network modeling will enable disease epidemiology studies in populations of cells inhabiting tissues and organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…However, previous studies have demonstrated that ovine periosteal‐derived cell morphological patterns of phenotype remain the same as those for human PDCs , . Although we ultimately aim to translate the current approach to the human condition, access to sufficient quantities of fresh human periosteum with and without prestress is currently not ethically or practically feasible, although cutting edge imaging technologies enabling seamless imaging from the organ to the nano‐length scale promise an exciting future in this regard , . Quantitative characterization of ovine periosteum as a stem cell niche provides a critical step in the clinical translation of periosteum's regenerative power in the context of the ovine model and its recent application to limited human patients .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that ovine periosteal‐derived cell morphological patterns of phenotype remain the same as those for human PDCs , . Although we ultimately aim to translate the current approach to the human condition, access to sufficient quantities of fresh human periosteum with and without prestress is currently not ethically or practically feasible, although cutting edge imaging technologies enabling seamless imaging from the organ to the nano‐length scale promise an exciting future in this regard , . Quantitative characterization of ovine periosteum as a stem cell niche provides a critical step in the clinical translation of periosteum's regenerative power in the context of the ovine model and its recent application to limited human patients .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, multimodal, high‐resolution imaging of anatomical cross‐sections at cellular scale resolution enables not only in situ assessment of tissue genesis by stem cells but also assessment of interactions of cells with absorbable and nonabsorbable materials commonly used in reconstructive surgery [57]. Cutting‐edge imaging modalities will enable seamless imaging of the periosteum and its cellular inhabitants, from the organ to subcellular length scale, enabling observation of PDCs in their native milieu and in interaction with novel functional materials of the future [7778].…”
Section: Discussionmentioning
confidence: 99%
“…Already, a few recent studies in connectomics have utilized mSEM to render volumetric image data from murine specimens sectioned with a microtome and reconstruct neuronal circuits with single-synapse resolution [14]. Multiscale imaging of interfaces between musculoskeletal tissue compartments could reveal precise architectures of tight junctions that control functional barrier properties, which exert profound effects on human physiology [1,2,12,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Its novel design enables the analysis of nanoscale morphologies across macroscopic specimens by implementing parallel electron beams and a multi-channel detector [10,11]. Multi-beam SEM is capable of reducing acquisition time by more than one order of magnitude and, therefore, of imaging larger surface areas with remarkable resolution [11], paving the path for seamless multiscale imaging of organ systems down to the cellular and even molecular scale [12]. As a consequence, this technology has drawn interest within the scientific community, particularly in areas related to brain connectomics [13,14] and cross-scale musculoskeletal mechanobiology [2,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation